ANALISIS KELAYAKAN EKONOMI DAN FINANSIAL PENDIRIAN PERUSAHAAN DAERAH JASA PELAKSANA KONSTRUKSI DI KABUPATEN PEMALANG - Kusyanto Kusyanto (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2014)
This research aims to analize the feasibility of economic and financial terms of a construction maintenance service regional company in Pemalang regency. To analyze the economic and financial feasibility, the researcher uses Net Present Value (NPV), Internal Rate Return (IRR), Net Benefit Cost Ratio (Net B/C Ratio), Discounted Payback Period (DPP), sensitivity analysis and Monte Carlo analysis. This reseach also analyze the feasibility of maintainance construction service regional companies based of legality aspect and establishment strategy and firm improvement by using SWOT analysis.Keywords: A financial and economic feasibility, BUMD, Crystal Ball, SWOT Analisys